Analysis of the Effectiveness of Education and Training For Employees in Improving Performance in the Directorate General of Teachers and Educational Personnel of the Ministry of Education, Culture, Research and Technology - Susilowati, Evi; Rivai Zainal, Veithzal; Hakim, Azis (Cv. Syntax Corporation Indonesia, 2023)
The aim of this research is to determine and analyze the effectiveness of employee education and training and the inhibiting and supporting factors as well as the strategies of the Directorate General of Teachers and Education Personnel of the Ministry of Education, Culture, Research and Technology in improving employee performance through the effectiveness of education and training. The research method uses descriptive qualitative methods. The research instrument was conducting in-depth interviews and documentation. The results of the research illustrate that the effectiveness of education and training for employees of the Directorate General of Teachers and Education Personnel of the Ministry of Education, Culture, Research and Technology regularly carries out training for all employees and this is effective in increasing knowledge and skills as measured through goals and objectives, trainers, training materials , the training methods and training participants have taken these aspects into account, the implementation has been returned to their respective fields so that they raise themes that are very useful in increasing employee competence in carrying out their duties. The speakers also come from academies, as well as technical experts who are truly competent in their fields. The education and training carried out also maximizes participants, so that all employees get the same opportunities. There are several inhibiting factors, including limited infrastructure at the training venue so that participants feel uncomfortable with the limited facilities available, in addition to inappropriate time management. The supports include employee motivation in participating in education and training, the desire to develop knowledge, skills and expertise as well as strategies in improving employee performance at the Directorate General of Teachers and Education Personnel of the Ministry of Education, Culture, Research and Technology through the effectiveness of education and training, namely by choosing a theme. training that is appropriate to the employee's field and duties, prioritizing employees whose performance is less than optimal or below standard, competency-based training, and conducting re-learning with all employees after the implementation of education and training in order to improve skills and foster a good sense of enthusiasm for employees.